Water Resistant High Strength Concrete - Ashot Antonyan (International Journal of Advanced Science and Technology, 2020)
The article presents the water resistance research of a group of highly functional concrete, namely high strength. In connection with the increase in the production volume of such concrete, a comprehensive study of all the properties, including water resistance, is extremely important.